INTERGRATED MANAGEMENT OF POTATO DEFOLIATING CATERPILLAR - Patel, P J; Chaudhari, S M.; Patel, R N.; Patel, C. K.; Patel, N. H. (Potato Journal, 2013)
Since one and a half decades, potato crop has occupied many new areas in different regions of Gujarat state. The crops affected badly by leaf eating caterpillar (Heliothis sp.) for the last few years and appearing moderate to an epidemic form causing huge damage. In the later stage of the crop, it is found deteriorating the quality by engraving the tubers also. Hence, an experiment was conducted with an integrated approach for three years (200203 to 2004-05) at Deesa. Four major sets of treatments were applied to determine efficient IPM module among which treatment with Chloropyrifos EC @ 0.5 Kg a.i. /ha at earthing up, foliar spray with Bt (60 days), foliar spray with Imidacloprid @ 0.04 kg a.i./ha (75 days) and foliar spray with Nimbicidine @ 0.4% (90 days) recorded minimum foliage and tuber damage as well as maximum number of healthy tubers (360 tubers/6 m2), healthy (26.89 q/ha) and total tuber yield (31.72 q/ha) with 22.94 per cent yield increase over untreated control. On the basis of weekly observations recorded, it was found that the caterpillar is appearing in the third week of December and then peaks in fourth week of January. Hence, the management tactics may be followed in the third or fourth week of December for Gujarat conditions as Chloropyrifos EC @ 0.5 kg a.i./ha at earthing up should be applied and foliar sprays are to be scheduled as Bt @ 109 spore count at 60 days, Imidacloprid @ 0.04 kg a.i./ha at 75 days and Nimbicidine at 90 days of the crop period which enable to keep the foliar defoliator population under control.